2020
DOI: 10.1037/hea0000820
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress trajectories in chronic physical health conditions.

Abstract: Objective. The onset of a chronic health condition (CHC) can have a severe impact on an individual's life, affecting mental and physical health. This study's goal was to investigate psychological distress trajectories starting from one year before to four years after the onset of a physical CHC. The specific aims were to identify the number and shape of longitudinal psychological distress trajectories and to test health-related, psychological, social, and demographic factors predicting these trajectories.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 48 publications
2
13
1
4
Order By: Relevance
“…The present study explored predicting factors across different types of physical CHC in an attempt to identify transversal factors that would predict psychological adaptation following any kind of CHC. Social support (Debnar et al, 2020;Li et al, 2018) or higher sense of spirituality (Harris et al, 2010) did not predict transition patterns of SWB in the present study. This unexpected finding may indicate that these factors may be protective factors in the case of specific types of CHC, but not in the face of any type of CHC.…”
Section: Predictors Of Longitudinal Transitionscontrasting
confidence: 89%
See 3 more Smart Citations
“…The present study explored predicting factors across different types of physical CHC in an attempt to identify transversal factors that would predict psychological adaptation following any kind of CHC. Social support (Debnar et al, 2020;Li et al, 2018) or higher sense of spirituality (Harris et al, 2010) did not predict transition patterns of SWB in the present study. This unexpected finding may indicate that these factors may be protective factors in the case of specific types of CHC, but not in the face of any type of CHC.…”
Section: Predictors Of Longitudinal Transitionscontrasting
confidence: 89%
“…These transition pathways suggest the occurrence of recovery patterns (upwards transition to a profile with higher levels of SWB) and delayed reaction patterns (downwards transition to a profile with lower levels of SWB) in the aftermath of the CHC onset, which have also been observed in past studies analyzing longitudinal trajectories (Galatzer-Levy et al, 2018). Compared with the general population, individuals living with a physical CHC have a higher risk of sustaining lower mental health (Debnar, 2020). Similarly, the present study results demonstrate that half of the participants showed lower levels of SWB at least over three years.…”
Section: Profiles Of Swb and Longitudinal Transitionsupporting
confidence: 71%
See 2 more Smart Citations
“…Findings regarding sex and injury-related characteristics generally indicate that they are not accurate predictors of psychological adaptation outcomes (Chevalier et al, 2009; Tonack et al, 2008; van Leeuwen et al, 2011). Yet, some studies have found that males are more likely to show a low depressive mood trajectory or a profile of minimal psychological impact than females following the onset of a chronic health condition (Debnar et al, 2020) or SCI (Galvis Aparicio et al, 2020). This may be related to the tendency for females to rate life events as more negative and uncontrollable than males (Matud, 2004).…”
Section: Discussionmentioning
confidence: 99%